Effect of carbonation on chloride transportation parameters in cementitious materials. Issue 3 (3rd July 2022) - Yoon, In-Seok; Chang, Chunho; Nam, Jin-Won
ABSTRACT: Many studies have only studied carbonation and chloride penetration separately, and study dealt with synergy interaction between these is very rare. This study is devoted to examining the chloride penetration parameters of carbonated cementitious materials, i.e. (a) surface chloride content, (b) chloride diffusivity, (c) chloride adsorption capacity and (d) critical chloride content linked with reinforcement corrosion directly. These chloride transportation parameters were expressed as a function of time in each condition because these depend on the mixing proportional properties and the degree of cement hydration. This study is expected to be useful to develop a chloride penetration model of carbonated concrete in the future.